Development of digital mathematics comics based on the realistic mathematics education approach - Putri, Gita Raviesta; Novita, Rita; Rahmattullah, Rahmattullah (Indonesian Journal of Science and Mathematics Education, 2025)
The lack of numeracy skills for elementary school students shows the urgency for innovative learning media that can provide math learning experiences that are relevant to real life. This study aims to develop and evaluate a digital mathematics comic based on the Realistic Mathematics Education (RME) approach as a learning media for elementary school students. Using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation, this study integrates real contexts, visual storylines, and interactive activities into digital media that can be accessed through various devices. The validation results from three media experts with seven aspects and 17 indicators showed that the digital comic was in the highly valid category (80-100%). The comic was also considered practical and effective by teachers and students in helping them understand mathematical concepts through contextual situations. Responses from media experts, teachers, and students mentioned that the storyline was relevant to everyday life, easy to use, interesting, and supported active student engagement. This research has implications for integrating the RME approach into digital comic media, which can transform abstract mathematics learning into a fun, meaningful, and student-centred experience, in line with the demands of 21st-century education.